In-service training and its relationship to psychological hardiness among teachers of students with special needs in the integration classes in the northern governorates of Palestine - Hamdan, Dr Salah Al-Din Hassan Mustafa; Oteer, Dr Rabee Shafiq Lutif (IJRDO- Journal of Educational Research, 2017)
The current study aimed to identify in-service teacher training and its relationship to psychological hardiness among special education teachers in the integration classes in the Tulkarm Governorate. The sample of the study consisted of 70 special education teachers who worked in the Tulkarm Directorate of Education. The two researchers used the study tool of in-service training (IST) as well as the Psychological Hardiness Scale. The results of the study revealed that score of in-service training was very high, and that score of the psychological hardiness was also very high. In addition, there was a direct correlation between in-service training and the psychological hardiness, i.e. the in-service training increased the psychological hardiness. There were yet no statistically significant differences due to the variables of gender and years of experience. On other hand, there were significant differences due to the variable of educational qualification in favor of the holders of the bachelor degrees or below. The study recommended the need to develop a comprehensive plan for teachers so that they could effectively deal with students with special needs in public schools, and the need to provide them with an intensive in-service training for special education.